Temperature effects on the hormetic response of Myzus persicae after sublethal exposure to insecticides - Ana Paula Nascimento Silva; Camila Faria Chagas; Emanuel Lucas de Andrade Alves; Vinícius de Castro Carvalho; Khalid Haddi (CABI Agriculture and Bioscience)
Abstract Studies on insecticide-induced stimulatory effects in pest insects have become of utmost importance due to their potential implications in pest management. Temperature influences the physiology and biology of ectothermic organisms like pest insects. It can also affect the toxicity and relative efficacy of insecticides that are used in agricultural fields. However, the impact of temperature on the insect stimulatory responses after exposure to mild insecticide-induced stresses has frequently been overlooked. Here, we investigated how different temperature levels (15; 20; 25; 28 °C) can modulate the toxicity of two synthetic insecticides chlorpyrifos (organophosphate) and deltamethrin pyrethroid); and subsequently how temperature impacts the survival and reproduction of the green peach aphid Myzus persicae exposed to sublethal concentrations of the two insecticides. Our findings indicated temperature-dependent effects of the two chemicals on mortality, longevity, and the number of nymphs produced by the aphids after lethal and sublethal exposures. In fact, besides the high toxicity induced by temperature at lower concentrations, the change’s magnitude and occurrence of stimulatory responses varied between temperatures and depended on the sublethal concentrations faced by the aphid females. Temperature increase from 15 to 28 °C increased chlorpyrifos and deltamethrin toxicity 4 and fivefold. Sublethal exposure of aphids extended the longevities for individuals treated with chlorpyrifos at 15 (all sublethal concentrations) and 25 °C (LC15 and LC20) and with deltamethrin at 20 (LC1) and 28 °C (LC20). Additionally, the total number of nymphs produced during the females' lifespan was increased after sublethal exposure to chlorpyrifos at 15 °C (LC1, LC5, and LC20) and at 20 °C (LC10) and to deltamethrin at 20 °C (LC1), 25 °C (LC5 and LC10) and 28 °C (LC1, LC5, and LC20). Our results reinforce the importance of a shift from studies focusing on the stimulatory effects of single stresses to studies investigating the effects of stressors’ combinations on insect hormetic response.